How Consumers' Attitudes towards Alternative Food Network Affect Their Consumption Satisfaction - Empirical Evidence from Zhengzhou - Bo Yang; Meng-Ting Liu; Guo Yu* (Tehnički Vjesnik, 2021)
With the continuous development of economic globalization and the increasingly diversified food culture of people, food hygiene and safety have become hot topics that have attracted much attention. The continuous occurrence of vicious food safety accidents has caused people to pay great attention to food safety. It is necessary to re-examine the issue that has risen to the height of national public safety, and it is necessary to increase the supervision of food safety. Based on 280 valid questionnaire data of alternative food network (AFN) in Zhengzhou, using structural equation model, this study investigates how consumers' attitudes towards AFN affect their consumption satisfaction. The results show that: the attitude towards AFN has a direct positive impact on consumer satisfaction, and indirectly affects satisfaction by affecting the perceived quality of consumers, and has an indirect positive impact on satisfaction through influencing the participation of AFN activities. The policy implications are: implement participatory security system, learn from the commercialization of mainstream food network, pay more attention to the quality of products, pay more attention to the needs of consumers and establish a "food community".